Indigenous Values in the Nyadran Traditional Ceremony Procession in Demangan Hamlet, Temanggung Regency - Chaesar, Ari Suryawati Secio; Andayani, Andayani; Yulisetiani, Septi (Bina Nusantara University, 2025)
The research aimed to describe and explain (1) the procession of the Nyadran traditional ceremony in Demangan Hamlet, Temanggung Regency, and (2) the local wisdom values embodied in the Nyadran traditional ceremony in the Demangan region. The research was conducted in Demangan, Temanggung, employing a qualitative method with an ethnographic approach. The research was conducted during the Nyadran traditional ceremony on Jumat Kliwon in the month of Ruwah. The data consisted of interview transcripts, field notes, and documents or archives of the Nyadran tradition. Data validity was ensured through triangulation and informant review, while the data analysis applied an interactive technique comprising four components: data collection, data condensation, data display, and conclusion drawing. The findings demonstrated that (1) the procession of the Nyadran traditional ceremony in Demangan Hamlet, Temanggung Regency, consisted of several stages: the formation of the organizing committee, mutual cooperation, setting up a tarup (tent) for a wayang performance, preparing ceremonial items (ubo rampe) for the main procession, and the main Nyadran procession itself; and (2) the Nyadran tradition embodies values of local wisdom, including discipline, education, mutual cooperation, cultural preservation, environmental awareness, peace, politeness, gratitude, and harmony. The Nyadran tradition serves as a reflection by the community to balance spiritual, social, and cultural preservation amidst globalization and modernization.